2016
DOI: 10.3390/app6120405
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits Bias the Perceived Quality of Sonic Environments

Abstract: Abstract:There have been few empirical investigations of how individual differences influence the perception of the sonic environment. The present study included the Big Five traits and noise sensitivity as personality factors in two listening experiments (n = 43, n = 45). Recordings of urban and restaurant soundscapes that had been selected based on their type were rated for Pleasantness and Eventfulness using the Swedish Soundscape Quality Protocol. Multivariate multiple regression analysis showed that ratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 35 publications
1
20
0
1
Order By: Relevance
“…While the concept has attracted an increasing interest in urban studies, and outdoor environments more in general, it also applies to indoor contexts, particularly when they serve "public" functions, like service buildings, public libraries, transportation hubs, restaurants, or other commercial facilities [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…While the concept has attracted an increasing interest in urban studies, and outdoor environments more in general, it also applies to indoor contexts, particularly when they serve "public" functions, like service buildings, public libraries, transportation hubs, restaurants, or other commercial facilities [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In their study, all Big Five dimensions showed linear and independent effects on noise sensitivity and together accounted for 33% of variance. Similarly, Lindborg and Friberg (2016) reported that noise sensitivity can be predicted by extraversion and conscientiousness. Belojević and Jakovjlevic (2001) also investigated factors influencing sensitivity to noise and found that neuroticism was the only significant personrelated factor in noisy environments but had no significant effect in quiet areas.…”
Section: Personality Traits and Demographic Factorsmentioning
confidence: 89%
“…Though Extraversion and Neuroticism (as well as all demographic variables) have often been discussed in relation to human sound evaluation, the results have been controversial (see the review by Fields, 1993). Even when all Big Five dimensions are considered together, a recent study by Lindborg and Friberg (2016) showed only small, albeit significant, effects.…”
Section: Personality Traits and Demographic Factorsmentioning
confidence: 99%
“…According to the definition of Job (1999), it refers to physiological and psychological (also including attitudinal) internal states of any individual, which determines reactivity to noise. Noise sensitivity predicts noise annoyance (Stansfeld, 1992;van Kamp et al, 2004), and it influences one's evaluation of the soundscape's pleasantness (Lindborg and Friberg, 2016). Moreover, noise sensitivity moderates one's daily behaviour; for instance, noise-sensitive individuals rarely have music in the background (Kliuchko et al, 2015) and often use hearing protection at work (Heinonen-Guzejev et al, 2011).…”
Section: Introductionmentioning
confidence: 99%